Developing hospital accreditation standards in Uganda. (6th October 2015) - Galukande, Moses; Katamba, Achilles; Nakasujja, Noeline; Baingana, Rhona; Bateganya, Moses; Hagopian, Amy; Tavrow, Paula; Barnhart, Scott; Luboga, Sam
Summary: Background: Whereas accreditation is widely used as a tool to improve quality of healthcare in the developed world, it is a concept not well adapted in most developing countries for a host of reasons, including insufficient incentives, insufficient training and a shortage of human and material resources. The purpose of this paper is to describe refining use and outcomes of a self‐assessment hospital accreditation tool developed for a resource‐limited context. Methods: We invited 60 stakeholders to review a set of standards (from which a self‐assessment tool was developed), and subsequently refined them to include 485 standards in 7 domains. We then invited 60 hospitals to test them. A study team traveled to each of the 40 hospitals that agreed to participate providing training and debrief the self‐assessment. The study was completed in 8 weeks. Results: Hospital self‐assessments revealed hospitals were remarkably open to frank rating of their performance and willing to rank all 485 measures. Good performance was measured in outreach programs, availability of some types of equipment and running water, 24‐h staff calls systems, clinical guidelines and waste segregation. Poor performance was measured in care for the vulnerable, staff living quarters, physician performance reviews, patient satisfaction surveys and sterilizing equipment. Conclusion: We have demonstrated the feasibility of a self‐assessment approach to hospital standards in low‐income country setting. This low‐cost approach may be used as a good precursor to establishing a national accreditation body, as indicated by the Ministry's efforts to take the next steps. Copyright © 2015 John Wiley & Sons, Ltd.